Social Support: a Key Variable for Health Promotion and Chronic Disease Management in Hispanic Patients with Rheumatic Diseases - Brooks, Alyssa T (Libertas Academica, 2014)
Chronic diseases, including rheumatic diseases, can cause immense physical and psychosocial burden for patients. Many Hispanics suffering with arthritis face activity limitations. Social support, or the functional content of relationships, may be important to consider when examining treatment and outcomes for Hispanic individuals. Participants were recruited from an urban community health center (CHC) as part of a larger health behavior study. A cross-sectional, descriptive, mixed methods analysis was conducted to explore the role of social support in the sample. Only Hispanic/Latino patients (n = 46) were included in this analysis. Interviews were conducted in both English and Spanish. The majority of the sample (87%) perceived some presence of social support in their lives. The two most commonly cited types of social support were emotional and instrumental. The two most common sources of social support were family members other than spouses (52.2%) and spouses (32.6%). Body mass index (BMI) was significantly correlated with the number of perceived sources of support. The presence or absence and the role of social support in supporting optimal health outcomes should be considered for Hispanics with chronic rheumatic diseases. Involving family members and spouses in the plan of care for this population could facilitate health promotion and chronic disease management.